2019
DOI: 10.1038/s41419-019-1626-x
|View full text |Cite
|
Sign up to set email alerts
|

Surmounting Cytarabine-resistance in acute myeloblastic leukemia cells and specimens with a synergistic combination of hydroxyurea and azidothymidine

Abstract: Acute myeloid leukemia (AML) patients display dismal prognosis due to high prevalence of refractory and relapsed disease resulting from chemoresistance. Treatment protocols, primarily based on the anchor drug Cytarabine, remained chiefly unchanged in the past 50 years with no standardized salvage regimens. Herein we aimed at exploring potential pre-clinical treatment strategies to surmount Cytarabine resistance in human AML cells. We established Cytarabine-resistant sublines derived from human leukemia K562 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Thus, more reduced kinases produced less CAFdATP in HL-60/CAFdA30 cells than in HL-60/CAFdA4 cells. The importance of the kinases was demonstrated previously in studies of cellular resistance to nucleoside analogs [7,17,39,43,44] and found to be associated with therapeutic outcomes [43,45,46]. Previously established nucleoside analog-resistant cell lines showed reduced cell surface hENT1 expression [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…Thus, more reduced kinases produced less CAFdATP in HL-60/CAFdA30 cells than in HL-60/CAFdA4 cells. The importance of the kinases was demonstrated previously in studies of cellular resistance to nucleoside analogs [7,17,39,43,44] and found to be associated with therapeutic outcomes [43,45,46]. Previously established nucleoside analog-resistant cell lines showed reduced cell surface hENT1 expression [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…Performing an analysis, such as the one presented here, prior to the treatment decision might have revealed a superior personalized treatment modality, for example by targeting the DNSP using a combination of azidothymidine (AZT) and hydroxyurea (HU) as we have recently demonstrated [42]. This plausible treatment modality could be specifically viable in light of the upregulation of TK1 (Fig.…”
Section: Patientmentioning
confidence: 93%
“…Similarly, leukemic cells that survived Ara-C cytotoxicity might be cross-resistant to other nucleoside analog prodrugs that share the same cellular uptake and activation routes. Consideration of drug action mechanisms and metabolism could further suggest potential combinations that may readily overcome chemoresistance modalities [42,[140][141][142][143].…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the authors studied the impact of 10 different polymorphisms in Ara-C metabolic pathway genes in a cohort of 225 adult patients with de novo AML showing the association of activating (deoxycytidine kinase, DCK) and deactivating (cytidine deaminase, CDA) genes variants with PIF [ 47 ]. As a matter of fact, increased levels of CDA are associated with Ara-C resistance in AML [ 48 , 49 ]. Moreover, in vitro studies showed a higher level of CDA activity in Ara-C resistant AML cell lines and demonstrated also the negative impact on the CDA A79C polymorphism [ 50 ].…”
Section: Mechanisms Of Therapeutic Resistancementioning
confidence: 99%